GENESIS, EVOLUTION AND SIGNIFICANCE OF ARTIFICIAL INTELLIGENCE IN SOCIAL LIFE - Jafar Mustafayev (Western European Studies, 2025)
This article discusses the benefits and risks of "Artificial Intelligence" for humanity, which has become a hot topic today. The article focuses on issues such as the relationship between artificial and natural intelligence, history, stages of development, and the dangers of artificial intelligence to humanity
Keywords: Artificial intelligence; Intellectual property; digital Uzbekistan